INBOUND TOURISM AS ECONOMIC DEVELOPMENT AND FUTURE MARKET DRIVER (Modern education and development, 2025)
This article examines and forecasts current inbound tourism using six variables: travel population, travel motivations, tourism consumption, public transportation, social environment, and time proportion. Other human elements, such as scenic spot capacity and natural resource conservation, have a significant impact. There will have a different impact. Tourism has evolved into one of the world's most important industries. It generated a substantial amount of revenue and had a significant influence. Current research on this topic need improvement.The findings reveal that over the last five years, cities inbound foreign exchange income has increased, as it is influenced by a variety of factors that can be used to forecast future development trends. Between 2020 and 2024, Uzbekistan's foreign exchange profits from inbound tourism increased steadily.